Desempenho de sistemas de irrigação por gotejamento operando com água residuária da castanha de caju sob diferentes pressões de serviço - Silva, Ketson Bruno da (2012)
The cashew crop is a major agricultural activities on national scene, having great economic value to the farmer, and consequently for the agribusiness the country. In northeastern Brazil there are a great number of processing cashew nut industries, generating a significant volume of wastewater. Thus, the scope of this paper was to evaluate the performance of drip irrigation systems operating with wastewater cashew nuts under different operating pressures. The activities were conducted at the Experimental Unit for Water Reuse (UERA), located in Park Zoobotânico, Universidade Federal Rural do Semi - Arid (UFERSA). In this study we tested three types of emitters (G1, G2 and G3), with different nominal flows, orifice areas and labyrinth length. The influence of operating pressures P1 (70kPa), P2 (140kPa), P3 (210 kPa) and P4 (280 kPa) on emitters clogging operating with cashew nuts wastewater were evaluated. The CUC, CUD, CVQ and Q were determined for each 20h of operating. The experiment was mounted on the split split plot scheme, the design completely randomized design with three replications. The data were subjected to analysis of variance and regression and test average. The results indicated that the cashew nuts wastewater represents risk of drippers clogging for the characteristics pH, calcium, magnesium, manganese, suspended solids and total coliforms; the formation of biofilm resulting from the interaction between the agents physical, chemical and biological provided partial clogging of the emitter and reduction on effluent application uniformity of the units irrigation; the units irrigation under service pressure P1 (70 kPa) had higher drippers clogging in relation the service pressures P2 (140kPa), P3 (210kPa) and P4 (280 kPa); the dripper G1 was more susceptible to clogging compared to the other, due to the greater labyrinth length; and the drip G1 was the most indicated for operation at the operating service pressure P2 (140 kPa), while the drip G2 was most appropriate under pressure service P1 (70 kPa)